What factors in Nepal account for the rural-urban discrepancy in human capital? Evidence from household survey data - Satis Devkota; Shankar Ghimire; Mukti P. Upadhyay (Economies, 2021)
We analyze the factors that determine human capital formation in the rural and urban sectors of Nepal and decompose the intersectoral difference into variables underlying supply and demand for human capital. In particular, we examine the role of access to primary and secondary schools as well as the socioeconomic, demographic, and geographic characteristics of households. Our results are based on Nepal Living Standards Survey data for 2004 and 2011. We find that access to schooling has a significant impact on the level of human capital, especially in rural areas. Our Blinder-Oaxaca decomposition attributes a large portion of the rural-urban gap to socioeconomic and demographic variables. Yet, the results reinforce our claim that an improvement in schooling access and road infrastructure is also necessary, particularly in the vast rural sector of Nepal, if human capital development is to provide a greater contribution to national welfare.
Keywords: 330; Blinder-Oaxaca decomposition; human capital index; Nepal Living Standards Surveys; rural-urban difference